Egeo - an advanced course for students of geography Book 1 - Lam Thi Hoa Binh (Đại học sư phạm, 2007)
Starting out Vietnam; Population; Labour force; Resources; Agriculture; Raising cattle and oultry; Industry; Heavy industry; Light industry; Food industry.